Implementasi Pembangunan Infrastruktur Kota Batam dalam Rangka Pengembangan Sebagai Kawasan Ekonomi Khusus (KEK) - Tan, Winsherly; Rusdiana, Shelvi; Maryto S, Bella Oktavia (Universitas Medan Area, 2024)
Indonesia's diversity can become a magnet in itself to attract domestic and foreign tourists to enjoy the beauty of Indonesia itself. In the era of President Joko Widodo's administration, he planned the National Long Term Development Plan (RPJPN) through the Vision and Mission of the Development Priority Agenda as stated in the 1945 Constitution of the Republic of Indonesia No. 17/2007 concerning National Development for 2005-2025 Long Term Development Plan. The spearhead is aimed at development, especially regional development, to reduce the development gap between developing regions and underdeveloped regions in Indonesia by accelerating and leveling regional development. The author uses an empirical method for the effectiveness of the Implementation of Batam City Infrastructure Development in the Context of Development as a Special Economic Zone (KEK) through the observation method. In conclusion, the infrastructure for Special Economic Zones (KEK), then improving the One Single Submission (OSS) system, and increasing Human Resources which is the solution to the strategic problems experienced by each Special Economic Zone (KEK), as well as several other things that are expected by the Batam economy can experience a further significant increase, the public can feel it.